DETEKSI KECURANGAN PENGELOLAAN DANA BOS MENGGUNAKAN HEXAGON FRAUD THEORY (STUDI EMPIRIS PADA SMA DAN SMK DI KOTA AMBON) - Gasperz, Jefry; Latuamury, Jabida; Silooy, Revy Wilhemina; Sapulette, Shella Gilby (JURNAL LENTERA AKUNTANSI, 2023)
This research aims to test the influence of hexagon fraud theory in detecting fraud in the management of BOS funds in high schools and vocational schools in Ambon City. This research uses a quantitative approach. The sampling technique was carried out using a saturated technique, where the entire population was sampled. The samples used were budget managers, namely school principals and school treasurers at high schools and vocational schools in Ambon City, totaling 51 samples. Data collection techniques were carried out using questionnaires. The research results show that pressure, opportunity and arrogance have a positive and significant effect on fraud in the management of BOS funds, while rationalization, ability and collusion have no effect on fraud in the management of BOS funds. Key words: Hexagon Fraud Theory, Fraud, BOS Funds